Diagnostic Accuracy of Modalities for Diagnosis of Thoracic Cancer: Retrospective Analysis - Ariawan, Wily Pandu; Hanafi, Arif Riswahyudi; Pradipta, Jaka; Jayusman, Mulawarman; Hanif, Muhammad Alfin; Hutabarat, Jubillete Windy; Amira, Salsabila Nur (http://dharmais.co.id/, 2025)
Background: Thoracic cancer becomes a huge consideration, especially for lung cancer, because it quietly increases over time and needs highly sensitive diagnostic modalities. Thus, we aim to investigate the diagnostic accuracy of several cytology-based modalities to diagnose thoracic cancer. It would serve as a reference for other cancer centers in estimating diagnostic approaches for thoracic cancer.Method: Retrospective analysis with a cross-sectional study comprised of 2358 diagnostic procedures at Dharmais Cancer Hospital, Jakarta, Indonesia, from 2020 to 2023. Data were extracted from e-medical records. We compared seven cytology-based procedures to the gold standard, which is histopathology examination. Results: Study subjects (n=2358; mean age 60 ± 12.0; 62.6% male) predominantly used the mode of diagnostic Bronchial Brushing Cytology (BBC) about 676 (28.7%). Endobronchial Ultrasound (EBUS) was the highest sensitivity (88.1%) of the diagnostic approach for thoracic cancer (p 0.05).Conclusion: EBUS had the highest sensitivity in diagnosing thoracic cancer. However, multimodality diagnostic procedures should be considered for patients who have symptoms suggestive of thoracic cancer to get highly positive results and lower complications, both cytologically and histologically. As a national cancer center, providing data on diagnostic modalities is necessary, and an analysis of cancer services is required for informed policy recommendations.